2023
DOI: 10.1002/ppap.202300095
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of plasma‐activated water on Escherichia coli for sterilization: Efficacy and mechanism

Yonghong Tan,
Yaqing Bian,
Ruoyang Fu
et al.

Abstract: The plasma‐activated water (PAW) produced by low‐temperature plasma (LTP) was applied to this research because of its safety and no thermal damage. Therefore, the physicochemical properties of PAW, as well as the efficacy and sterilization mechanism of Escherichia coli, were discussed. The PAW (pH 1.27, conductivity 6400 μS/cm) could reduce E. coli by 1.31‐log reduction using LTP at 70 W for 9 min. The results demonstrated that PAW caused DNA and protein leakage with malondialdehyde production. This study may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the reaction of low-temperature plasma with water produces a number of reactive species, such as H O 2 2 , OH ⋅ , O 3 , NO 2 − , NO 3 − , and so on. [12][13][14] These active substances are the basis of PAW sterilization. [15][16][17][18] In addition, it is also found that superoxide anion radicals are important for the antimicrobial effects of PAW.…”
mentioning
confidence: 99%
“…Previous studies have shown that the reaction of low-temperature plasma with water produces a number of reactive species, such as H O 2 2 , OH ⋅ , O 3 , NO 2 − , NO 3 − , and so on. [12][13][14] These active substances are the basis of PAW sterilization. [15][16][17][18] In addition, it is also found that superoxide anion radicals are important for the antimicrobial effects of PAW.…”
mentioning
confidence: 99%